Records of the Australian Writers' Guild - Australian Writers' Guild (1982)
MS Acc99.228 comprises theatrical scripts from the records of the Australian Writers' Guild, some of which were originally submitted to the Guild for competitions.
The Acc99/235 instalment includes additional theatrical scripts, including, Dreamtime people by Coral Drouyn, Naso bello, naso brutto: a nose is a nose by Josie Composto Eberhard, and, Passion: six new plays by Australian women edited by Ros Horin.
The Acc00/105 instalment consists of a further batch of scripts, including, The world of Ian, Blue murder by Beatrix Christian, and, Unknown soldier by Ron Elisha.
The Acc00/170 instalment is a further instalment of scripts, including, Giordano Bruno by Paul Brown and Robert Deller, That eye the sky by Justin Monjo and Richard Roxburgh, Distant lights from dark places, and, Lucy in the leap year.
The Acc00/258 instalment comprises further scripts, including, The last wake at She-Oak Creek by Bob Herbert, Miles Franklin and the rainbows end by Julia Britton, and, Upside down at the bottom of the world by David Allen.
The Acc01/234 instalment includes further scripts, including, Don's party, Hammer, Barefoot, The heiress from Punchbowl, and, An ocean out my window.
Manuscript reference no.: MS Acc99.228, MS Acc99.235, MS Acc00.105, MS Acc00.170, MS Acc00.258, MS Acc01.234.
The Australian Writers' Guild (AWG) was formed in 1962 as the professional association for all performance writers, that is, writers for radio, screen, stage and television. The Guild promotes and protects the interest and standing of writers who originate or adapt written material for performance.
Donor box lists available.
Keywords: Australian Writers' Guild -- Archives; Authors -- Labor unions -- Australia -- Archives; Screenwriters -- Labor unions -- Australia -- Archives; Television writers -- Labor unions -- Australia -- Archives; Radio authorship -- Australia; Australian literature; Writing -- Australia; Authorship; Authors